A new deep sea barnacle, Tetrachaelasma tasmanicum sp. nov. (Cirripedia: Balanomorpha) from the South Tasman Rise, South Pacific Ocean - Buckeridge, J. S. (New Zealand Journal of Marine and Freshwater Research, 1999)
A new deep sea balanomorph, Tetrachaelasma tasmanicum sp. nov., is described. This new record is based on numerous disarticulated plates, from dredge samples around deep-sea seamounts on the South Tasman Rise. This is the deepest known occurrence of the Balanomorpha, and the first record of Tetrachaelasma from the Pacific realm. An overview of the biogeography, including aspects of the palaeontology of deep sea balanomorphs is provided. A map showing station localities and a list of deep sea cirripedes recovered from the South and East Tasman Rise during the 1995 Rig Seismic cruise, are included.